Brucellosis an Unusual presentation as isolated septic mono-arthritis of the knee joint: A case report - Muad Abdi Hassan; Fatima Noor; Aram Salehi; Bassem Al Hariri (Heliyon, 2024)
Brucellosis is a zoonotic infection that is widely spread across the world. It is becoming more common in Middle Eastern countries such as Qatar, Saudi Arabia, and the Mediterranean region. Despite this, we need to remain vigilant as it is still prevalent in many parts of the world. The most common presentation is musculoskeletal, but it can also present as septic arthritis in the sacroiliac, hip, or knee joints. Brucella melitensis was only found in one extended culture of synovial fluid. Treatment involved a combination of antimicrobial therapy using gentamycin, doxycycline, and rifampin. A high level of suspicion for brucellosis is necessary for any patient coming from an endemic region with non-specific and chronic arthritis to ensure early diagnosis and treatment. In this case, we present a 28-year-old male who was diagnosed with Brucellosis after developing acute septic arthritis.